Transient fading X-ray emission detected during the optical rise of a tidal disruption event - Malyali, A.; Rau, A.; Bonnerot, C.; Goodwin, Adelle; Liu, Z.; Anderson, Gemma; Brink, J.; Buckley, D.A.H.; Merloni, A.; Miller-Jones, James; Grotova, I.; Kawka, Adela (2024)
We report on the SRG/eROSITA detection of ultra-soft (kT = 47+−55 eV) X-ray emission (LX =2.5+−00.56 × 1043 erg s−1) from the tidal disruption event (TDE) candidate AT 2022dsb ∼14 d before peak optical brightness. As the optical luminosity increases after the eROSITA detection, then the 0.2–2 keV observed flux decays, decreasing by a factor of ∼39 over the 19 d after the initial X-ray detection. Multi-epoch optical spectroscopic follow-up observations reveal transient broad Balmer emission lines and a broad He II 4686 Å emission complex with respect to the pre-outburst spectrum. Despite the early drop in the observed X-ray flux, the He II 4686 Å complex is still detected for ∼40 d after the optical peak, suggesting the persistence of an obscured hard ionizing source in the system. Three outflow signatures are also detected at early times: (i) blueshifted H α emission lines in a pre-peak optical spectrum, (ii) transient radio emission, and (iii) blueshifted Ly α absorption lines. The joint evolution of this early-time X-ray emission, the He II 4686 Å complex, and these outflow signatures suggests that the X-ray emitting disc (formed promptly in this TDE) is still present after optical peak, but may have been enshrouded by optically thick debris, leading to the X-ray faintness in the months after the disruption. If the observed early-time properties in this TDE are not unique to this system, then other TDEs may also be X-ray bright at early times and become X-ray faint upon being veiled by debris launched shortly after the onset of circularization.